1971
DOI: 10.1084/jem.134.4.963
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Tissue Grafts Established in Rabbit Ear Chambers

Abstract: Early experiments using in vivo microscopy on mammalian tissues were reviewed by Clark et al. (1). The introduction of the transparent rabbit ear chamber, first described by Sandison (2, 3) has allowed microscopic observations to be made of the structure and function of a thin layer of living tissue in the mammal for periods up to several years (4).A modification of the Sandison-Clark rabbit ear chamber which allowed the mica cover slip to be removed, exposing the surface of the stable vascular membrane and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This has been ob served in previous studies on transplanted tissue but other mechanisms have also been observed such as formation of sprouts in the transplant [6,36] or fusion of sprouts from host and transplant [14,19,20]. These dif ferent mechanisms might be related to the size of the transplant.…”
Section: Discussionmentioning
confidence: 86%
“…This has been ob served in previous studies on transplanted tissue but other mechanisms have also been observed such as formation of sprouts in the transplant [6,36] or fusion of sprouts from host and transplant [14,19,20]. These dif ferent mechanisms might be related to the size of the transplant.…”
Section: Discussionmentioning
confidence: 86%
“…When pieces of kidney were allografted into the rabbit ear chamber, they reestablished their blood circulation in 2-4 days by anastomosis of their cut vessels to the adjacent vasculature of the ear chamber membrane (6). Autografts appeared to function indefinitely, since autologous renal tissue was observed in the rabbit ear chamber withe ut change for 6 mo after fixation, and functioning myometrial autografts were observed for periods of up to 1 yr (6). Allografted renal tissues in the rabbit ear chamber reject after periods of up to 3 mo (6).…”
Section: (From the Department Of Experimental Pathology John Curtin mentioning
confidence: 99%
“…Autografts appeared to function indefinitely, since autologous renal tissue was observed in the rabbit ear chamber withe ut change for 6 mo after fixation, and functioning myometrial autografts were observed for periods of up to 1 yr (6). Allografted renal tissues in the rabbit ear chamber reject after periods of up to 3 mo (6). A whole kidney allografted in similar rabbits is rejected in 7 days.…”
Section: (From the Department Of Experimental Pathology John Curtin mentioning
confidence: 99%
“…Focal lesions are seen which may involve only a single vessel in a glomerulus, and the origin of such lesions is not understood. Hobbs and Cliff [25] reported that preferential blood flow patterns had been observed in glomeruli maintained in rabbit ear chambers. It is possible that focal lesions may represent the presence of greater amounts of complex deposited simply because of the greater volume of blood passing along the preferred pathway.…”
Section: Response Of Glomerular Components To Persistent Deposition Omentioning
confidence: 99%